(untitled) (Research, Society and Development, 2022)
This study aimed to assess the efficacy of acupuncture, yoga, and meditation on the quality of life of adults classified as obese. Eleven electronic databases (MEDLINE via PubMed, Embase, Cochrane Library, Scopus, LILACS, Chinese National Knowledge Infrastructure (CNKI), China Biomedical Literature (CBM), Theses and Dissertations Database (BDTD), Capes Theses and Dissertations Catalog, OpenGrey and Google Scholar) were systematically searched. The search strategies were developed using the MeSH, DeCS and Emtree descriptors. Randomized clinical trials that evaluated changes in the quality of life of healthy adults classified as overweight or obese who were treated with acupuncture, yoga or meditation were included. We identified 1369 records and 5 studies were included in this review. Of these, two were included in the meta-analysis. In the qualitative synthesis, four studies reported a higher quality of life for some scores in the intervention group than in the control groups. In the meta-analysis, lower scores were identified in the acupuncture intervention group when compared to the control group, and this difference was statistically significant (MD= - 4.79; 95%CI - 9.14; - 0.44). However, the global mean differences of the studies that evaluated the effect of acupuncture on the physical, social and environmental dimensions of quality of life did not identify a statistically significant association.